2014 President's plenary international psycho‐oncology society: moving toward cancer care for the whole patient. Issue 12 (12th May 2015) - Bultz, Barry D.; Travado, Luzia; Jacobsen, Paul B.; Turner, Jane; Borras, Josep M.; Ullrich, Andreas W.H.
Abstract: The International Psycho‐oncology Society (IPOS) has just celebrated its 30th anniversary. The growth of psychosocial oncology has been exponential, and this relatively new field is becoming a core service that focuses on prevention, reducing the burden of cancer, and enhancing the quality of life from time of diagnosis, through treatment, survivorship, and palliative care. Looking back over the past 30 years, we see that cancer care globally has evolved to a new and higher standard. Today, 'cancer care for the whole patient' is being accomplished with an evidence‐based model that addresses psychosocial needs and integrates psycho‐oncology into the treatment and care of patients. The President's Plenary Session in Lisbon, Portugal, highlighted the IPOS Mission of promoting global excellence in psychosocial care of people affected by cancer through our research, public policy, advocacy, and education. The internationally endorsed IPOS Standard of Quality Cancer Care, for example, clearly states the necessity of integrating the psychosocial domain into routine care, and that distress should be measured as the sixth vital sign after temperature, blood pressure, pulse, respiratory rate, and pain. The plenary paper also discussed the global progress being made in Europe, North America, and Australia in providing quality cancer care for the whole patient. Collaborative partnerships between IPOS and organizations such as the European Partnership Action Against Cancer and the World Health Organization are essential in building capacity for the delivery of high‐quality psycho‐oncology services in the future. Copyright © 2015 John Wiley & Sons, Ltd.